Design and Simulation of a 2-Degree of Freedom Energy Harvester from Blood Flow for Powering the Pacemaker - Abdelmawgoud, Manar; Parque, Victor; Nada, Ayman; Fath El-Bab, Ahmed M. R. (Universitas Muhammadiyah Yogyakarta, 2025)
The pacemaker is a device that is used to treat different abnormal heart rhythms. It is usually powered using traditional batteries. These batteries run out of power after about 7 years, necessitating the replacement of either the pacemaker or its batteries for the patient’s survival. This means that the patient will need to undergo surgery for the replacement process which can compromise the patient’s life and increase the probability of being infected, not to mention the operation cost. To overcome this problem, energy harvesters can be a safer substitute for these traditional batteries since they can convert different forms of energy into electric energy, which can be stored and used when needed. In this paper, a 2-degree-of-freedom (DOF) piezoelectric energy harvester from blood flow is designed and modeled. The harvester is designed as a cut-out beam that is fixed on the pacemaker lead that passes through the Superior Vena Cava (SVC). To protect the harvester from being highly distorted by the blood flow, a plastic barrier is added in front of the harvester from the vein’s inlet side. The harvester consists of three layers, a PZT5A layer sandwiched between two plastic layers. The harvester is designed to have its first and second natural frequencies between 1Hz and 1.67Hz, the normal frequency range of the human heartbeat. The harvester harvests up to 3.8V which is considered satisfying since the pacemaker usually stimulates the heart using a voltage that ranges from 1V to 10V. This voltage can be used to power the pacemaker and extend its lifetime. The harvester was simulated using ANSYS Workbench Software 2020 R2. On the simulation level, the harvester obtained a maximum output power of 0.81µW at a load of 2.2MΩ.